Memaknai Kelas Menengah Muslim Sebagai Agen Perubahan Sosial Politik Indonesia - Wasisto Raharjo Jati (AL-TAHRIR, 2016)
Abstract: This article aims at analyzing agenda of socio-political changes among Indonesian middle class muslim . Compared with other middle class groups, middle class muslim is a middle class which tends to have political sense toward political changes. It is caused by its political experiences they have got such as alienation, authoritarianism, and inequality. Those ironic experiences make Indonesian middle class become political agent. Political experiences which have happened in middle east such as Turkey, Iran, and Egypt become main preferention to analyze current situation. Therea are two prominent perspectives to see socio-political changes which are addressed to Indonesian middle class muslim:   post Islamism and Islam populism . The first perspective, political changes is synergically based on mutual cooperation between Islam, democracy, and liberalism. On the other hand, the second one, revolusion is placed as  the main strategy of affirmative political change done by middle class. More specifically, Islamist ideology rejects religious modernity and seeks to oppose Islam against secular, pluralistic and liberal understandings of the “emancipated self” and the democratic public sphere. Those both perspectives are then used to analyze case of Indonesian middle class muslims. This article will elaborate more deeply to analyze socio-political changes among Indonesian middle class muslims.الملخص: هذا الكتاب يحصل ليتخذ الفرق فى الثقفة والسياسيّة على الفنّ المتوسط للمسلمين الاندونسي اختلافا بالفنّ المتوسّط الاخرى. الفنّ المتوسط للمسلمين كان فنّا متوسطا سياسيّا على اختلاف السياسيّة. ذالك الفصل يشمل بكون السياسيّة المحصول كمثل رأي الناس. و يشمل ايضا هذا الكتاب يتّخذ على المعاشرة بالمعروف. كثرة حال السائريصير فنّا متوسّطا للمسلمين للدلالة السياسيّة. السياسيّة فى كون مثل المعاشرة فى العرب, كمثل مصرى, تركى, عير اختيار الاولى للتخاذ الفرق على الثقفة السياسيّة فى ذالك المكان. امّا الاوّل رأيان فى نظر فرق ثقفة السياسيّة بعلاملت فنّ متوسّط المسلمين. وهو بعد الاسلاميّة و الاسلامية الذى نصر المستضعفين. الرأي الاوّل, يحصل على الحضارة و دموكراتية و الحرّية. الرأي الثانى, يحصل على التغيّر بطريق الاوّل من تغيير السياسيّة  تأكيدا يعمل على الفنّ المتوسّط. رأيان يستقبل ليتّخذ فنّ المسلمين فى اندنسي. هذا الكتاب يصير فى تغيير ثقفة السياسية على فنّ متوسّط المسلمين فى اندنسي.Abstrak: Tulisan ini bertujuan untuk menganalisis agenda perubahan sosial politik bagi kelas menengah muslim Indonesia.  Dibandingkan dengan kelas menengah lainnya, kelas menengah muslim adalah kelas menengah yang politis terhadap perubahan politik. Hal tersebut terkait dengan adanya pengalaman politis yang dialami seperti halnya alienasi, otoritarianisme, maupn juga ketimpangan. Berbagai kondisi satir itulah yang menjadikan kelas menengah muslim tampil sebagai agen politik. Pengalaman politik seperti yang terjadi dalam kasus masyarakat Timur Tengah seperti Mesir, Turki, dan Iran menjadi preferensi utama dalam menganalisis perubahan sosial politik yang ada. Terdapat dua perspektif penting dalam melihat agenda perubahan sosial politik yang dialamatkan oleh kelas menengah muslim yakni post-Islamisme dan Islam populisme. Perspektif pertama lebih mengandalkan adanya sinergi antara Islam, demokrasi, dan liberalisme. Perspektif kedua lebih mendudukkan revolusi sebagai jalan utama perubahan politik afirmatif yang dilakukan oleh kelas menengah. Kedua perspektif itulah yang kemudian dilihat dalam menganalisis kasus kelas menengah muslim Indonesia.  Tulisan ini akan mengelaborasi lebih dalam mengenai agenda perubahan sosial poltik dalam kelas menengah muslim Indonesia.